Estrutura espacial das assembleias de peixes de riachos submetidos a diferentes graus de impacto ambiental - Alves, Nathália Trevisan (2019)
Stressful impacts on natural environments, whether of anthropogenic origin or not, tend to cause instability in the environment, leading to the loss of environmental complexity. In this context, the present study analyzed the spatial structure of the fish assemblages of the headwaters of three streams inserted in the metropolitan region of Londrina-PR, with different degrees of environmental impacts: Cambé (urban), Cafezal (peri-urban), and Taquara (rural). In this context, we expect that the fish assemblages of the urban stream are relatively more disorganized and unstructured. The collections were carried between 2013 and 2017. Fish collection was initially performed with manual fishing followed by electric fishing. Physical and chemical parameters of streams and water were analyzed, as well as the land use and occupation categories of the basins. Fish assemblage structure was analyzed from the evaluation of indicator species based on occurrence and abundance, biomass and abundance curves, as well as null models of species cooccurrence. The canonical discriminant analysis detected significant differences among studied streams regarding the physical and chemical parameters, as well as the percentage of categories of land use and occupation. The Taquara had the highest number of bioindicator species, among which only one was exotic, indicating its good condition for the maintenance of native species. The most impacted streams, Cambé and Cafezal, presented a high percentage of exotic species as bioindicators, 57% and 50%, respectively. Considering abundance-biomass curves, no stream showed the expected pattern for intact environments. Taquara was characterized as moderately degraded, followed by the Cambé, while the Cafezal was remarkably the most disturbed. Patterns of species co-occurrence showed a tendency for the fish assemblages of the Cambé and Cafezal streams to be disrupted, while the Taquara showed equilibrium in the same period. The analysis of canonical correlation segregated the streams in a way analogous to the ABC curves, being the Cafezal the most disturbed, associated to the greatest impermeable area available and values of electrical conductivity. On the other hand, Taquara presented greater correlation with areas of dense vegetation. Distinctively from the initial hypothesis, the study revealed a growing gradient of environmental disturbance from Taquara to Cambé, followed by the Cafezal. These results point out that, although it is of the same order and located in the same watershed, each one tends to present specific responses to environmental impacts, requiring specific conservation actions for each case.